GAMBARAN STRES KERJA DAN STRATEGI PENANGGULANGAN MASALAH PADA PEKERJA RUMAH TANGGA - Sinaga, Hotma Rotua; Garey, Evans (Noetic Psychology, 2011)
This study aims to describe about housemaidÃ¢â¬â¢s stressor and how they cope with those stressors in life. The variables in this research are workÃ¢â¬â¢s stress and coping style. The instrument used in this research was a questionnaire which made by researcher. Reliability test with Alpha Cronbach indicates reliable value of 0,884 for workÃ¢â¬â¢s stress scale and 0,873 for coping style scale. The data collected from 162 respondents and the analysis data used in this research was descriptive statistics. The result showed that 33.33 percent of the subjects had a high work stress tendency, and the coping style is most often used is emotional-focused coping (51.85 percent).ÃÂ Keywords: stress, coping, housemaid